Inheritance and molecular mapping of stripe rust resistance genes in Chinese winter wheat Zhongliang 16. (August 2015) - Ma, Dongfang; Li, Qiang; Zhao, Mingmin; Carmen, Simón-Mateo; Wang, Baotong
Abstract: Stripe rust, caused by Puccinia striiformis f. sp. tritici ( Pst ), is one of the most widespread diseases of wheat worldwide. Resistance breeding is constantly pursued for decades to tackle the variations of prevalent Pst races. Zhongliang 16 has wide adaptability, strong resistance to abiotic stresses, excellent biological characteristics, and higher resistance to stripe rust. In this study, Zhongliang 16 was crossed with a susceptible genotype, Mingxian 169, to identify the resistance gene(s). Seedlings of the parents, F1, F2, F2:3, and BC1 progenies were tested for resistance with Chinese Pst race CYR29 and CYR30 in greenhouse conditions. Zhongliang 16 possessed different dominant genes for resistance to each race, temporarily designated as Yrzhong16-1 and Yrzhong16-2 . Yrzhong16-1 conferring resistance to CYR29 was flanked by Xbarc212 and Xwmc177 on the short arm of 2A at genetic distances of 5.4 and 6.6 cM; and Yrzhong16-2 conferring resistance to CYR30 was flanked by Xgwm644 and Xbarc95 on the long arm of 7B at genetic distances of 2.3 and 3.5 cM, respectively. Chromosomal locations and race and allelism tests indicated that the two genes are different from previously reported stripe rust resistance genes. These genes and their flanking markers should be useful in marker assisted selection-breeding programs against wheat stripe rust. Graphical abstract: Highlights: Wheat cultivar Zhongliang 16 has high resistance to stripe rust. Zhongliang 16 possessed Yrzhong16-1 and Yrzhong16-2 for resistance to stripe rust. We mapped Yrzhong16-1 on the short arm of wheat chromosome 2A. We mapped Yrzhong16-2 on the long arm of wheat chromosome 7B. The two genes are different from previously reported stripe rust resistance genes.